Bioremediation of chromium(VI) to chromium(III) using geobacillus caldoxylosilyticus - Nur Izwinda A Rahim, 1993-; Wan Azlina Ahmad, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2016